GEOINFORMATION SYSTEMS BASED ON CARTOGRAPHIC AND GEODESIC SURVEYS FOR PLANNING INVESTMENT PROCESSES IN CITIES - Kukhar, M.; Pomortseva, O.; Kobzan, S.; Dobrokhodova, O. (Municipal economy of cities. Series: «Economy science», 2022)
The use of GIS (Geographic Information System) systems to administration investment in cities is becoming increasingly popular. Modern technologies allow the use of GIS system based on geodetic surveys of the same area, over time, with the introduction of characteristically attributive information. The obtained data can characterize both the most up-to-date spatial information and be used in the process of territory analysis. Thus, the same map can be used by users of different fields of activity, for example, to characterize the investment attractiveness of cities administration in connection with relevant, specialized information about the territory of cities. Making investments in cities often requires cooperation between different institutions, offices and other structures. To do this, it is possible to create electronic systems that can be implemented through electronic channels. This concept is called the Regional Business Spatial System. GIS tools can be considered as an integrating element between the subjects of the environment. GIS tools can be an element that integrates the environment in which investments are made. Not only existing objects can be marked on joint maps, but also implemented, planned or even postulated projects thanks to up-to-date geodetic survey materials. The aim of the work is a conceptual analysis conducted to determine whether at a certain stage the use of GIS technologies in cities can serve as a platform conducive to the creation of regional electronic systems to promote investment in the city, based on current geodetic and cartographic data.